Development of new technologies in multimedia journalism (Herald of Journalism, 2018)
The most urgent problems of modern media environment cannot be solved without adequate content modelling and managing technologies applied in mass multimedia and without revealing the specifics of content synergy impact on the audience.
Keywords: Key words: multimedia journalism, content, new technology, storytelling.